Klasifikasi Sebaran Status Kesuburan Tanah Di Kecamatan Teluk Elpaputih (Studi Kasus Areal Kebun Awaya) - Risamasu, Robby G; Maitimu, Leonora; Luhukay, Marcus; Tomasoa, Reny (Universitas Pattimura, 2023)
The purpose of this study was to categorize the soil fertility status in Teluk Elpaputih District, Central Maluku Regency. This case study uses the National soil classification system and Soil Taxonomy. The study area is placed on flat-wavy physiography (slopes 0–15 %) by the flexible observation method of the grid. In order to ensure the ground association, observation lines are 800 meters apart and checking paths are located every 400 meters. According to the National Soil Classification System, four types of soil are found: Regosol, Alluvial, Gleisol, and Cambisol. The equivalent of Soil Taxonomy has two orders Entisol and Inceptisol, four suborders Psamment, Aquent, Fluvent, Udepts, four great group Udipasmments, Hydraquents, Udifluvents, Dystrudepts, and four subgoups Aquic Udipasmments, Typic Hydraquents, Typic Udifluvents, and Oxic In addition, the soil fertility status in the study area units ranged from low to high, namely PL0G1 (high), PL0G2 (medium) land units, PL0G3 (medium), and UL1G3 (low).